Cecal bascule herniation through the foramen of Winslow - Aaron M. Williams; Zachary Pickell; Mary R. Shen; Naveen Sangji (University of São Paulo, 2021)
Bowel obstructions can have a variety of causes, including impacted feces, adhesions, volvulus, non-internal hernias, and in rare cases internal hernias. We report a 63-year-old woman who presented to the emergency department with severe abdominal pain, nausea, vomiting, and obstructive symptoms that had started 12 hours earlier. A computed tomographic scan of the abdomen and pelvis showed a right internal hernia with a cecal bascule traversing through the foramen of Winslow, concerning for a closed-loop obstruction. The patient underwent an exploratory laparotomy with cecal bascule reduction and cecopexy. Given the increased mortality risk if undiagnosed, it is important to remain aware of internal hernias. Patient outcomes are markedly improved with early diagnosis and surgical intervention.